The Relationship Between Workload and Nurse Turnover Intention at the RS PMI Bogor in 2025 - Rizki Amalia; Solehudin Solehudin; Ahmad Rizal (Sean Institute, 2026)
Introduction: Human resource problems often faced by hospital management are high nurse turnover rates. Turnover is the departure of employees from an organization. Turnover is one of the alternatives that employees do to get a better job. One of the reasons employees want to move or leave is that employees feel the workplace atmosphere is no longer in accordance with their expectations. Objective: The purpose of this study is to determine the Relationship between Workload and Nurse Turnover Intention at PMI Hospital in 2025. Method: The research method uses quantitative research with analytical descriptive research and uses a Cross Sectional design, where the research is conducted at the time of data collection between independent variables and dependent variables which are carried out together at the same time. The population is 43 nurses with a total sampling technique, namely with a sample of 43 respondents. Results: The results of univariate research were obtained from 43 respondents, There is a significant relationship between the Relationship between Workload and Nurse Turnover Intention at PMI Hospital in 2025. The results of the Chi-square statistical test obtained a P-value = 0.019. The Odds Ratio value of 7.192 means that respondents who have a heavy workload have a 7 times greater chance of having bad Turnover Intention compared to respondents with a moderate workload.